Understanding COVID-19 vaccine demand and hesitancy: A nationwide online survey in China. - Yulan Lin; Zhijian Hu; Qinjian Zhao; Haridah Alias; Mahmoud Danaee; Li Ping Wong (Public Library of Science (PLoS), 2020)
Background This study attempts to understand coronavirus disease 2019 (COVID-19) vaccine demand and hesitancy by assessing the public's vaccination intention and willingness-to-pay (WTP). Confidence in COVID-19 vaccines produced in China and preference for domestically-made or foreign-made vaccines was also investigated. Methods A nationwide cross-sectional, self-administered online survey was conducted on 1-19 May 2020. The health belief model (HBM) was used as a theoretical framework for understanding COVID-19 vaccination intent and WTP. Results A total of 3,541 complete responses were received. The majority reported a probably yes intent (54.6%), followed by a definite yes intent (28.7%). The perception that vaccination decreases the chances of getting COVID-19 under the perceived benefit construct (OR = 3.14, 95% CI 2.05-4.83) and not being concerned about the efficacy of new COVID-19 vaccines under the perceived barriers construct (OR = 1.65, 95% CI 1.31-2.09) were found to have the highest significant odds of a definite intention to take the COVID-19 vaccine. The median (interquartile range [IQR]) of WTP for COVID-19 vaccine was CNY¥200/US$28 (IQR CNY¥100-500/USD$14-72). The highest marginal WTP for the vaccine was influenced by socio-economic factors. The majority were confident (48.7%) and completely confident (46.1%) in domestically-made COVID-19 vaccine. 64.2% reported a preference for a domestically-made over foreign-made COVID-19 vaccine. Conclusions The findings demonstrate the utility of HBM constructs in understanding COVID-19 vaccination intent and WTP. It is important to improve health promotion and reduce the barriers to COVID-19 vaccination.